Pengembangan Proses Pembelajaran Matematika Kurikulum 2013 Berbasis Lesson Study Pada Siswa Kelas VII SMP Negeri 6 Salatiga Tahun 2015/2016 - apriani, Yuliana; , Prof. Dr. Sutama, M.Pd (2016)
The learning process is the important of a lesson. To get the optimal mathematical learning process, it will be the development of the learning process of mathematics curriculum in 2013 based on lesson study. Research and development is purposed, 1) to analyze and describe the implementation of learning taken from math teachers in students of class VII SMP Negeri 6 Salatiga. 2) to analyze and describe the development process of learning mathematics in the curriculum based on lesson study in 2013 in the seventh grade students at SMP Negeri 6 Salatiga. 3) Analyze and test the effectiveness of the learning process of mathematics curriculum based on lesson study in 2013 in class VII SMP 6 Salatiga developed by teachers. This type of research is a research and development Research and Development (R & D) with evaluative design. The time of the study in second semester of the school academic year 2015/2016. The subjects were students and teacher of SMP Negeri 6 Salatiga. Data collection techniques used observation, interviews, questionnaires, documentation and Focus Group Discussion (FGD). The technique of data analysis methods, comparasion, and techniques delpietechnique.The validity of the data in this study using triangulation and triangulation techniques. The results of research and development is a 1) the implementation process of learning mathematics curriculum 2013 class VII SMP 6 Salatiga in the preliminary activities, the core activities of learning mathematic curriculum needs to be developed in 2013, and the closing is appropriate existing RPP, 2) curriculum development process of learning mathematics 2013 based on lesson study class VII SMP 6 Salatiga performed at the preminary activities, core activities, and cover activites that include aspects of the learning prosess. 3) the effectiveness of the learning process of mathematics curriculum in 2013 based on lesson study has increased towards the better, from the aspect of students' motivation to complete the task on time, self-learning aspects, aspects of the involvement of students in asking questions, and aspects of student involvement to solve the problem.